Design and Performance Testing of a 3D Printed Mini DC Powered Pump for Microbubble Generator - Tulus Hidayat Yusanto; James Julian; Fitri Wahyuni; Adi Winarta; I Wayan Marlon Managi (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2023)
Centrifugal pumps are the most commonly utilized in industries, agriculture, and households. In the microbubble generator, the centrifugal pump is driven by a DC motor for efficiency. This research was conducted to determine the optimal centrifugal pump design for microbubble generators using 3D-printed PLA material. The pump drive uses a brushless DC motor. With impeller dimensions r1=16mm, r2=26mm, beta1=46.8, beta2=62.8, and number of blades = 8, the resulting head is 2m at a constant operational current of 3A and a flowrate of 0 L/m. The same operational current input yields a maximum flow rate of 14 L/min with a head of 0.5 m. Maximum head exists when there is no liquid on the outlet side. At current >= 6.5A, there is a deviation from the previously formed trend. The input power of 58W is generated when the maximum flow rate is 25L/m. Maximum efficiency can be achieved as the input current increases to <= 6.5A and 18L/m. At conditions >= 6.5A, efficiency decreases drastically as the input current increases. This centrifugal pump design can work optimally at a constant input current of 6.5A with an input power 58W for the microbubble generator.